2017
DOI: 10.7863/ultra.16.08087
|View full text |Cite
|
Sign up to set email alerts
|

Automated Fractional Limb Volume Measurements Improve the Precision of Birth Weight Predictions in Late Third‐Trimester Fetuses

Abstract: Automated fractional limb volume measurements can improve the precision of weight predictions in third-trimester fetuses. Correction factors may be necessary to adjust underestimated systematic errors when using automated fractional limb volume with prediction models that are based on manual tracing of fetal limb soft tissue borders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 17 publications
3
19
0
1
Order By: Relevance
“…Cutoff points of FASTT for LGA and SGA varied in different studies. Close to this result was Mack et al [12] who found that the best cutoff value for FASTT in detecting macrosomia was ≥ 10.0 mm with high sensitivity (81.0%) and specificity (86.8%).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Cutoff points of FASTT for LGA and SGA varied in different studies. Close to this result was Mack et al [12] who found that the best cutoff value for FASTT in detecting macrosomia was ≥ 10.0 mm with high sensitivity (81.0%) and specificity (86.8%).…”
Section: Discussionmentioning
confidence: 72%
“…An accurate estimation of fetal weight helps obstetricians in making decision on the route of delivery [11]. Incorporation of fetal soft tissue parameters improves the accuracy of fetal weight estimation [12]. The aim of this study was to assess the accuracy of fetal abdominal subcutaneous tissue thickness as an indicator of fetal birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54][55] The acceptance of individual variation extends also to proportions, possibly increasing predictive capacity by adding 3-dimensional measurements of various body sections. 56 Applying Fetal Growth Charts The recent fetal growth charts that are based on multiple populations should be, by design, the first choice for an area where no population-specific references exist rather than previously used charts that are based on single populations from high-income societies. Further, what emanates from the recent studies and the discussion that follows them is that there is no clear indication that 1 fetal growth standard is equally applicable for all pregnancies of the world, not for clinical use and not for public health issues that include life course and health risks in adult life.…”
Section: Ethnicity and Variationmentioning
confidence: 99%
“…Importantly, as noted by the authors, the current methods for sonographic EFW are based on studies of Hadlock et al, 2 Shepard et al, 3 and others from the 1980s, although recent efforts attempted to utilize fractional limb volume. 4 The EFW is in actuality an estimated fetal body volume. Whereas volume calculations require a cube factor of linear measurements, commonly used formulas incorporate complex exponential functions and multifactorial equations, in an attempt to utilize a single complex equation to fit fetal weights from the early second to late third trimesters.…”
Section: Letters To the Editorsmentioning
confidence: 99%